2018
DOI: 10.1186/s12917-018-1683-x
|View full text |Cite
|
Sign up to set email alerts
|

Satellite telemetry tracks flyways of Asian Openbill storks in relation to H5N1 avian influenza spread and ecological change

Abstract: BackgroundAsian Openbills, Anastomus oscitans, have long been known to migrate from South to Southeast Asia for breeding and nesting. In Thailand, the first outbreak of H5N1 highly pathogenic avian influenza (HPAI) infection in the Openbills coincided with the outbreak in the poultry. Therefore, the flyways of Asian Openbills was determined to study their role in the spread of H5N1 HPAI virus to poultry and wild birds, and also within their flocks.ResultsFlyways of 5 Openbills from 3 colonies were monitored us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We observed several colonies of the Asian openbill within areas of human habitation and agricultural landscapes, similar to reports for other stork or crane species in South Asia (Katuwal, Sundar, et al., 2022 ; Kittur & Sundar, 2021 ; Sharma et al., 2024 ). This is primarily attributed to the presence of large‐sized nesting trees protected by local communities and possibly the abundance of prey species within agricultural landscapes (Hara et al., 2018 ; Pramanik et al., 2016 ; Ratanakorn et al., 2018 ; Sundar et al., 2019 ). Additionally, we observed some colonies in forests, indicating that Asian openbills also utilize diverse habitats for breeding.…”
Section: Discussionmentioning
confidence: 99%
“…We observed several colonies of the Asian openbill within areas of human habitation and agricultural landscapes, similar to reports for other stork or crane species in South Asia (Katuwal, Sundar, et al., 2022 ; Kittur & Sundar, 2021 ; Sharma et al., 2024 ). This is primarily attributed to the presence of large‐sized nesting trees protected by local communities and possibly the abundance of prey species within agricultural landscapes (Hara et al., 2018 ; Pramanik et al., 2016 ; Ratanakorn et al., 2018 ; Sundar et al., 2019 ). Additionally, we observed some colonies in forests, indicating that Asian openbills also utilize diverse habitats for breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study on tracking flyways of Asian openbill in Thailand reported that some individuals moved between south and central Thailand (Ratanakorn et al., 2018), even fly to northeast India and Bangladesh during the non‐breeding season (McClure, 1998). It could be argued that the “over‐migration” occurred in Thailand when the storks initially migrated north, bringing a few migrants to locations out of their regular migratory range as vagrants (Ralph & Wolfe, 2018), and arriving in southwest China.…”
Section: Discussionmentioning
confidence: 99%
“…Thailand reported that some individuals moved between south and central Thailand (Ratanakorn et al, 2018), even fly to northeast India and Bangladesh during the non-breeding season (McClure, 1998).…”
Section: The Previous Study On Tracking Flyways Of Asian Openbill Inmentioning
confidence: 99%